Strategic judgment proofing - Yeon-Koo Che; Kathryn E. Spier (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
A liquidity-constrained entrepreneur needs to raise capital to finance a business activity that may cause injuries to third parties the tort victims. Taking the level of borrowing as fixed, the entrepreneur finances the activity with senior (secured) debt in order to shield assets from the tort victims in bankruptcy. Interestingly, senior debt serves the interests of society more broadly: it creates better incentives for the entrepreneur to take precautions than either junior debt or outside equity. Unfortunately, the entrepreneur will raise a socially excessive amount of senior debt, reducing his incentives for care and generating wasteful spending. Giving tort victims priority over senior debt holders in bankruptcy prevents over-leveraging but leads to suboptimal incentives. Lender liability exacerbates the incentive problem even further. A Limited Seniority Rule, where the firm may issue senior debt up to an exogenous limit after which any further borrowing is treated as junior to the tort claim, dominates these alternatives. Shareholder liability, mandatory liability insurance and punitive damages are also discussed.
Keywords: 330; the judgment proof problem; strategic judgment proofing; capital structure; subordination; lender liability; limited seniority; shareholder liability; Haftung; Haftpflichtversicherung; Unternehmensfinanzierung; Konkurs; Theorie